Candidate gene discovery of Botrytis cinerea resistance in grapevine based on QTL mapping and RNA-seq - Su, Kai; Zhao, Wei; Lin, Hong; Jiang, Changyue; Zhao, Yuhui; Guo, Yinshan (Frontiers in Plant Science, 2023)
Grape gray mold disease (Botrytis cinerea) is widespread during grape production especially in Vitis vinifera and cause enormous losses to the grape industry. In nature, the grapevine cultivar ‘Bata’ (V.riparia × V. labrusca ) showed high resistance to grape gray mold. Until now, the candidate genes and their mechanism of gray mold resistance were poorly understood. In this study, we firstly conducted QTL mapping for grape gray mold resistance based on two hybrid offspring population which showed wide separation in gray mold resistance. Notably, two stable QTL related to gray mold resistance was detected and located on linkage group LG2 and LG7. The phenotypic variance ranged from 6.86 to 13.70% on LG2 and 4.40 to 11.40% on LG7. Combined with the RNA-seq, one structural gene VvEDR2 (Vitvi02g00982) and four transcription factors VvERF92 (Vitvi07g02065), VvMAD20 (Vitvi15g01208), VvMYB136 (Vitvi10g00345) and VvMYBPA4 (Vitvi11g00098) which may involve in VvEDR2 expression and grape gray mold resistance were selected. This discovery of candidate gray mold resistance genes will provide an important theoretical reference for grape gray mold resistance mechanisms, research, and gray mold resistant grape cultivar breeding in the future.